How I treat acute and persistent sickle cell pain - Samir Ballas (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Sickle pain is the hallmark of sickle cell disease (SCD). It could be acute, persistent/relapsing, chronic or neuropathic. Although there is a general consensus that pain is a major manifestation of SCD there is a controversy as to the types of pain and their interrelationship between acute, chronic, relapsing, persistent, etc. This report first reviews the general approach to the management of acute vaso-occlusive crisis (VOC) pain including education, counseling, pharmacotherapy, non-pharmacotherapy, and fluid therapy. This is followed by the presentation of five patients that represent typical issues that are commonly encountered in the management of patients with SCD. These issues are: individualized treatment of pain, bilaterality of pain, use of illicit drugs, tolerance to opioids, opioid induced hyperalgesia and withdrawal syndrome. The clinical aspects and management of each of these issues are described. Moreover, such complications as tolerance and withdrawal may persist after discharge and may be mistaken as chronic pain rather than resolving, persistent or relapsing pain.